"Thinking peace into existence": Virginia Woolf and Jessica Dismorr. Issue 1 (2nd January 2023) - Hinnov, Emily M.
ABSTRACT : Virginia Woolf continued her quest for peace, resisting the brutality of war, until the end of her life. Woolf's contemporary, the English painter Jessica Dismorr, similarly uses her art to protest patriarchal and militaristic modes of consciousness so that we might "think peace into existence." In this essay, I suggest an interdisciplinary approach to engaging with World War II era feminist/modernist artists' responses to the blasts of war through the lenses of Woolf's essay "Thoughts on Peace in an Air Raid" (1940) and Dismorr's series of paintings Related Forms and Superimposed Forms (c. 1936-1939). Both female modernists reject the aggressive, patriarchal, militaristic male roots of war in favor of creating alternatively nurturing, communal, and even utopian emblems to peace.